Lexical competence and Functional Discourse Grammar - García Velasco, Daniel (ALFA: Revista de Linguística, 2009)
This article discusses the role of the lexicon component within Functional Discourse Grammar. It argues that the treatment of lexical meaning in most grammatical models is not adequate and proposes an alternative analysis based on Marconi’s (1997) notion of lexical competence, according to which lexical meaning comprises two different dimensions: referential and inferential lexical knowledge. It is further claimed that decompositional models of lexical meaning do not really capture speakers’ inferential knowledge, as it is doubtful that they possess detailed and similar definitions for most lexical items. It is claimed that speakers associate beliefs and specifications with lexical items and that communication emerges when those beliefs converge dynamically in verbal interaction. Finally, the implications of this analysis for FDG are examined. It is suggested that abstract meaning definitions are not really needed in the model and that the lexicon should be in close contact with the conceptual component.